Nodal Marginal Zone Lymphoma with Simultaneous Transformation at Diagnosis and Pleural Effusion as the Initial Presentation: A Case Report - Dodos, Konstantinos; Kalamara, Vasileia Tsampika; Georgakopoulou, Vasiliki Epameinondas; Kavoura, Paraskevi (Acta medica Lituanica, 2025)
Nodal Marginal Zone Lymphoma (NMZL) is a rare, indolent subtype of B-cell non-Hodgkin lymphoma. This case report presents a 67-year-old female diagnosed with NMZL, which had transformed into Diffuse Large B-cell Lymphoma (DLBCL) at the time of diagnosis. The patient’s initial presentation involved a dry cough and pleural effusion, a symptom rarely reported in NMZL cases. Diagnostic procedures, including cytology and immunohistochemistry, confirmed the presence of monoclonal B lymphocytes and identified markers consistent with NMZL transformation to DLBCL. The findings highlight the diagnostic challenges associated with NMZL due to the lack of specific immunohistochemical markers, emphasizing the need for histopathological analysis to distinguish NMZL from other lymphomas, such as follicular lymphoma. This case underscores the importance of early detection and differentiation in lymphomas presenting with pleural effusion, as transformation to aggressive forms like DLBCL significantly impacts the prognosis and treatment approaches. Despite the rarity of transformation at diagnosis, clinicians must consider it in NMZL cases with atypical presentations.
Keywords: B-cell non-Hodgkin lymphoma; histologic transformation; pleural effusion; diffuse large B-cell lymphoma; nodal marginal zone lymphoma